Being a Female Gastroenterologist in Turkey - Akkan Çetinkaya, Züleyha; Ersoy, Özdal; Tözün, Nurdan (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Our aim is to examine the representation of woman gastroenterologists in both work and social life in Turkey and to elucidate the difficulties they encounter during their career pathways or while actively practicing their profession. Materials and Methods: A self-structured survey consisting of 25 questions was sent via email to all 152 female gastroenterologists. Survey results were received from 140 participants. Results: Sixty percent of the woman gastroenterologists had marriage–career conflicts, and 74% of them stated that they could not manage work–life balance with their children. Among these woman gastroenterologists, 46.6% of them reported that they had faced carrier-related barriers and challenges while applying for an academic rise or expecting a promotion in their job, 58.5% were exposed to gender mobbing, and 35.6% were subjected to verbal or physical violence. On the other hand, woman gastroenterologists are found to be underrepresented in endoscopic interventions where only one-third of the participants perform invasive endoscopic procedures, and the percentage of those who perform advanced endoscopy such as endoscopic submucosal dissection and endoscopic mucosal resection remains even less as 8.9%. The number of women in leadership positions during their careers is found to be low, and only 2 women were selected as the president of the society since 1959, the establishment time of the Turkish Society of Gastroenterology. Conclusion: More effort is needed to keep a fair gender balance in Turkish gastroenterology society and to increase the women’s representation in therapeutic endoscopy options and also in leadership positions. Cite this article as: Akkan Çetinkaya Z, Ersoy Ö, Tözün N. Being a female gastroenterologist in Turkey. Turk J Gastroenterol. 2024;35(2):112-118.